Safe patient handling legislation and changes in programs, practices, perceptions, and experience of musculoskeletal disorders by hospital characteristics: A repeated cross-sectional survey study. (January 2021) - Lee, Soo Jeong; Kang, Kyung Ja; Lee, Joung Hee
Abstract: Background: Safe patient handling legislation has been enacted in 11 states in the United States to protect healthcare workers from patient handing injuries. Implementations and outcomes may vary across hospitals by the characteristics of the institution. Objectives: This study was to investigate the changes in safe patient handling programs in hospitals, and nurses' perceptions, work practices, and musculoskeletal symptoms by hospital characteristics after the passage of California's safe patient handling legislation. Design: Repeated cross-sectional surveys. Settings: Two statewide surveys of registered nurses were conducted in California, where a safe patient handling law became effective in 2012. Random samples were selected from the lists of the California Board of Registered Nurses (2000 nurses in 2013 and 3000 nurses in 2016). Participants: Among survey respondents (26% in 2013 and 20% in 2016), the study sample included 254 nurses in 2013 and 281 nurses in 2016, who met the eligibility for this study: nurses employed in a hospital and had direct patient care or patient handling duties. Methods: Data were collected by postal and on-line surveys. Data were compared by hospital size, geographic area, hospital teaching status, and ownership (for-profit, non-profit, government). Results: Between 2013 and 2016, nurses' reports showed improvements in safe patient handling policies and programs across the different characteristics of hospitals. In 2016, nurses in large, teaching, non-profit, and rural hospitals reported slightly better scores for safe patient handling program variables than their counterparts; however, changes in the use of mechanical lifting devices and experiences of musculoskeletal symptoms and injury were not significantly different by hospital characteristics. Overall, teaching hospitals consistently showed greater improvements than non-teaching hospitals for both hospital-level (safe patient handling programs and organizational practices) and individual-level (perceptions and symptoms) variables. Conclusions: Our findings indicate overall improvements of safe patient handling programs in California hospitals after the passage of safe patient handling legislation. Positive changes appear to be greater among teaching, non-profit, and rural hospitals. However, greater positive changes in safe patient handling programs shown in certain hospital characteristics were not necessarily linked to more improvements in nurses' safe work practices and experiences of musculoskeletal symptoms or injuries.